Intermediation in markets for goods and markets for assets - Ed Nosal; Yuet-Yee Wong; Randall D. Wright (Federal Reserve Bank of Atlanta, 2019)
We analyze agents' decisions to act as producers or intermediaries using equilibrium search theory. Extending previous analyses in various ways, we ask when intermediation emerges and study its efficiency. In one version of the framework, meant to resemble retail, middlemen hold goods, which entails (storage) costs; that model always displays uniqueness and simple transition dynamics. In another version, middlemen hold assets, which entails negative costs, that is, positive returns; that model can have multiple equilibria and complicated belief-based dynamics. These results are consistent with the venerable view that intermediation in financial markets is more prone to instability than in goods markets.
Keywords: G24; D83; 330; middlemen; intermediation; search; bargaining; multiplicity